Insights into the Morphological Evolution of Mossy Dendrites in Lithium Metal Symmetric and Full Cell: A Modelling Study. Issue 3 (1st March 2023) - Verma, Prakhar; Puravankara, Sreeraj; Nandanwar, Mahendra N.; Chakraborty, Jayanta
Abstract : Mossy-dendrite growth is a common phenomenon observed in many lithium metal batteries. A lattice model is presented in this work to understand the morphological changes in mossy dendrites during the plating and stripping of Li metal. The model mimics the mossy dendrite growth by incorporating nucleation and growth of spherical particles at the lattice points. The model can predict the transition between root and tip growth by merely changing the Damköhler number. The mass transfer limitations created by the initiation of the mossy phase are identified as the dominant cause of the decay in cell potential. We also investigate the effect of morphology on the formation of dead lithium during electrodissolution. This is the first attempt to combine pseudo-2D and lattice models to simulate full-cell cycles toward mossy growth.